West Atlantic coastal marine biodiversity: the contribution of the platform iNaturalist - Rocha, R. M.; Azevedo, F.; Oliveira, U.; Cardoso, M. N.M.; Clerier, P. H.B.; Fortes, R. R.; Lopes-Filho, E. A.P.; Lorini, M. L.; Miranda, L. S.; Moura, R. B.; Senna, A. R.; Silva, F. M.; et al. (Springer Nature, 2024)
Data collection by citizen scientists is emerging as an important practice for biodiversity detection, mapping, and compilation of big data in open online platforms such as iNaturalist, acting as a source of biodiversity discovery. However, the validation of species identification is a central issue for the scientific use of these data. Here we compared the list of marine species in the Western Atlantic Ocean obtained in iNaturalist with that generated from scientific collections to understand whether there are taxonomic bias favoring some types of organisms, and to understand the amount of trustful information at the species level in iNaturalist. We also present the first bioblitz results of marine biodiversity in Brazil, an iNaturalist Citizen Science campaign advertised by social media, as a case study. We found that marine taxa with higher richness were well represented in iNaturalist (Arthropoda, Mollusca and Chordata), nonetheless Annelida, Bryozoa, Nematoda, Nemertea, Platyhelminthes, Porifera, Chlorophyta, and Rhodophyta were under-represented. Taxa with small, cryptic, parasitic and/or sessile organisms were poorly represented. According to the methods applied in this study, we showed that 72% of the records are probably well identified, except for Bryozoa and Platyhelminthes. Brazilian marine records in iNaturalist add up to only 1/30 of the total West Atlantic records analyzed but there was a steep increase from 2021 to 2022, as a possible contribution of our bioblitz campaign especially for Arthropoda, Echinodermata, and Annelida. We conclude that the record of marine biodiversity by citizen scientists is a valuable tool, but the engagement of taxonomists is strongly recommended to increase the correct identification of species.
Keywords: Biological data mining; Citizen science; GBIF; Identification validation; Marine diversity; OBIS